Co-Construction Concept Through Cloud-Based Social Network Platform Design, Implementation, and Evaluation - Chang, Ben; Shih, Yen-An; Lu, Fang-Chen (International Review of Research in Open and Distributed Learning, 2018)
Today’s learners can easily share their thoughts on their social networks, and this movement, undoubtedly, has been affecting their learning. However, learners in such an ad hoc social network environment need a deliberate design to support their idea sharing and concept exchange. Gaining insights into how to stimulate concept sharing in a social network helps learners learn. To this end, this study examined how to design a cloud-based concept construction platform, and analyzed the users’ interaction behaviours on the platform. A cloud-based platform named CoCoing.info was implemented to achieve the aim. The platform has three major functions: (a) co-construction concept building, (b) social network organization, and (c) concept circulation among social networks. Seven hundred and twenty-six accounts registered on the platform. Users constructed 2,121 concepts using 20,049 nodes, and 1,618 files were established. The access statistics results indicated that the platform was used throughout the day, in which the ratio of in-class to after-class access was 0.59:0.41. Among the interactions, 31.24% belonged to concept construction and 68.76% were user responses. Meanwhile, the key player social networking analysis results indicated that teachers appear to play a crucial role in initiating concept construction and triggering social interaction within the type of concept construction social network.